(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article highlights the purpose, tasks, and activity directions of the State Debt Service Guarantee Fund, which plays an important role in the public debt management system of the Republic of Uzbekistan. In addition, the study analyzes the growth trends of public debt in Uzbekistan and examines the revenues and expenditures of the State Debt Service Guarantee Fund.